Academic Correspondence - Abrahams, Peter; Wynter, H. L.; Nettleford, Rex; Hearne, John; Anderson, Roy K.; Joyce, Lyle; Morrison, Hugh; Hall, Patricia; Waterlow, John; Ali, Wahid; Waite-Smith, Cicely (My University, 1963)
Correspondence between Peter Abrahams and various persons affiliated with the University College of the West Indies.
57 pgs. Typescript, handwritten, sepia-toned, in fairly good condition.